The classical economists - O’Brien, D. P. 1939– (Princeton University Press, 2017)
The Classical Economists Revisited conveys the extent, diversity, and richness of the literature of economics produced in the period extending from David Hume's Essays of 1752 to the final contributions of Fawcett and Cairnes in the 1870s. D. P. O'Brien thoroughly updates, rewrites, and expands the vastly influential work he first published in 1975, The Classical Economists. In particular, he sets out to make clear the shaping of a comprehensive vision of the working of an open economy, building on the great work of Adam Smith in Wealth of Nations, a development that was substantially affected by the contributions of David Ricardo. He shows that the Classical literature was in fact the work of a host of thinkers from a wide range of backgrounds. Covering the intellectual roots of the Classical literature and its methodological approaches, and the developed theories of value, distribution, money, trade, population, economic growth, and public finance, and examining the Classical attitudes toward a rich variety of policy issues, The Classical Economists Revisited considers not only the achievements of the Classical writers but also their legacy to the later development of economics. A seminal contribution to the field, this book will be treasured for many years to come by economists, historians of economics, instructors and their students, and anyone interested in the sweeping breadth and enduring influence of the classical economists.